The efficacy of air spray chilling and its impact on microbial quality of broiler carcasses - Alena Nagyová; Peter Korim; Martin Mellen; Jozef Nagy; Peter Popelka; Monika Pipová (Italian Journal of Animal Science, 2015)
This study was focused on the evaluation of the period necessary for chilling of poultry carcasses through recording of temperature in the breast muscles and microbial associations on the surface in relation to body weight (BW). The temperature was measured in sixty broiler carcasses divided into six equal weight categories (1.3, 1.4, 1.5, 1.6, 1.7 and 1.8 kg). For the temperature measurements the module ELPRO was used. The module was placed in the body cavity and the probe was inserted into breast muscle. The mean temperature of breast muscles immediately after slaughter ranged from +38.8 to 40.30°C. The mean temperatures after chilling of carcasses with average BW1.5 kg (5.10±1.231; 7.90±2.356; 9.30±2.966). Average total viable count (TVC) on the surfaces before chilling was 3.99±0.19 log CFU/100 cm2 (1.2 to 1.5 kg), and 3.93±0.14 log CFU/100 cm2 (1.6 to 1.8 kg). A statistically significant increase (P<0.05) in TVC after chilling in both weight categories (n=6) was found. Average TVC after chilling was 4.28±0.11 CFU/100 cm2 (1.2 to 1.5 kg), and 4.33±0.08 (1.6 to 1.8 kg). Average Enterobacteriaceae count was reduced in the lower weight group (1.3 to 1.5 kg) from 3.11±0.35 to 2.97±2.97 during chilling, but it significantly (P<0.05) increased (3.07±0.28 to 3.13±0.14) in the higher weight group (1.6 to 1.8). Salmonella was not detected in either of the samples.